(3efJNH GdCSGfjOs - (3eMeO GdHGHdj , eMeO GdHGHdj GdbGgQj GdTGaYj, TeS GdOjf CHh YHO Gddg,J (B1077 (3g` s
(3ChdgG (B:s
(3CeG HYO ade JRd SfJg GdESfGO ai gPg GdCeI jeJWi Edi ZQGjHgG ZhGQH GdEZJQGH hjdO ai EbJfGA TPQg s
(3BNQgG (B:s
(3EPG cfJ CYde YdekG jbjfkG HCf LejY MjGJi cSGYg ade dG Cchf VfjkG HgG hGLYdgG ai UdGM hWGYg hgfG GfJgi eG ef Gddg JYGdi Hg Ydi GdYHO ef efJNH GdCSGfjO ai hUd GdeUfaGJ hGdCNQGA hGdeSGfjO s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B84s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B4 - (3U (B567s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdMOjK h GdeUWdMs